Wave Soldering Structure Optimization Simulation of Multi-layer Ceramic Capacitors. Issue 3 (October 2020) - Su, Wei; Luo, Wenhao; Li, Junkui; Liu, Renhuai
Abstract: In this paper, the thermal analysis and structural analysis of MLCC are carried out by using the commercial finite element software ANSYS. By comparing the thermal-mechanical analysis results of the structural optimization models of different schemes, the optimal optimization scheme is found. The model calculated the time required for MLCC to reach temperature stability considering thermal convection and heat conduction, and obtained the thermal deformation and thermal stress distribution of MLCC element. Based on the analysis results of MLCC original model, the thermal analysis under different wave soldering temperatures was carried out. Based on the simulated transient results, the structure and materials of MLCC key components were optimized. The results provide a basis for the optimal design of MLCC.